Three level atom in bad cavity - Messikh Azeddine, Azeddine; Umarov, Bakhram A.; Gharib, Subhi Mahmoud Ahmed; Wahiddin, Mohamed Ridza (IDOSI Publications, 2013)
We calculate the gain at the central frequency for a three-level Λ configuration in a bad cavity with a squeezed input. We show that it is possible to obtain the same effects as in the case of the driven three-level Λ system in a free space and damped to a broadband squeezed vacuum. We also show that the coherence induced by the broadband squeezed vacuum can be generated in the case of an input squeezed vacuum. Our results deal with the three-level Λ system and we can easily generalize to the other possible atomic configurations such as V and cascade.